A Longitudinal Study of Parenting Conditions on Two Adult, North American River Otters' (Lontra Canadensis) Repetitive Behavior. Issue 1 (2nd January 2023) - Island, Heide D.; Smith, Brook; Winn, Emmeline M.; Newberry, Kristen; Manfredini, Julia; Slyngstad, Rebecca J.; Strack, Sarah
ABSTRACT: Captive animal welfare research focuses on husbandry, enrichment, enclosure space, visitor effects, and opportunities for species-typical behavior (e.g., foraging, territoriality, and social interaction). And yet, one of the most biologically relevant opportunities for species-typical behavior, parenting, has received little attention. The goal of this longitudinal investigation was to explore the differential variability of repetitive behavior across three parenting conditions (i.e., No parenting, parenting, and foster parenting) among captive, wild-rescued, North American river otters. This study represents anatural ABAC design, the conditions reflect differential parenting phases: No parenting (A), Parenting biological pups (B), and Alloparenting nonbiological pups (C). The behavior of two adult North American river otters at the Oregon Zoo were observed from April2016 through March2020 during the different parenting contexts. The frequency of repetitive behaviors was lowest during parenting and highest during the non-parenting conditions. Although data for season, weather, and visitor variables were also collected throughout this study; parenting condition was the only consistent moderator of abnormal repetitive behavior observed.